The Influence of Product Quality and Price on Miyako Product Purchasing Decisions (Case Study in Hermon Store Bengkulu) - Ario Syahdeli; Mardhiyah Dwi Ilhami (Penerbit Jurnal Indonesia, 2024)
Marketing becomes very important with increasing public knowledge. Good product marketing can ensure that business actors will get maximum profits, conversely, if product marketing is not good, it will have an impact on reducing income for business actors. This research aims to determine the influence of product quality and price on purchasing decisions for Miyako products (case study at the Hermon Bengkulu Store.This research is a type of quantitative research with a population of all consumers of Miyako Products (Case study at the Hermon Bengkulu Store). This research used a purposive sampling technique with a total sample of 110 respondents. Data collection techniques in this research are observation and questionnaires. The data analysis techniques used are multiple linear regression, coefficient of determination, and hypothesis testing. Based on the results of the data processing, from computer calculations, namely calculations using SPSS, the regression equation is Y = 7.698 + 0.508 X1 + 0.403 This value means that the independents, together, contribute 62.0% in influencing the dependent variable while the rest. The results of the hypothesis test obtained: Product quality and price together influence the decision to purchase Miyako (Y) Toko Hermon Bengkulu products.